2004
DOI: 10.1016/j.femsle.2004.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Transformation ofLactobacillus plantarumby electroporation with in vitro modified plasmid DNA

Abstract: An improved method for the electrotransformation of Lactobacillus plantarum CECT 220 (ATCC 8014) with plasmid DNA isolated from Escherichia coli is described. The two main modifications with respect to existing methods are: (i) isolation of plasmid DNA from E. coli JM110 grown in minimal medium and (ii) in vitro modification of the DNA by cell-free extracts of the host L. plantarum. Optimal electrotransformation was obtained with exponentially growing cells of L. plantarum concentrated to 6x10(9) cfu ml-1, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In contrast, the type IV RM systems produce restriction enzymes which cleave solely methylated DNA. There are several reports, mostly referring to DNA adenine methylation ( dam )/ DNA cytosine methylation ( dcm ) that methylation pattern of plasmid DNA has a major impact on transformation efficiency and allows plasmid DNA to circumvent host restriction mechanisms [24-26]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the type IV RM systems produce restriction enzymes which cleave solely methylated DNA. There are several reports, mostly referring to DNA adenine methylation ( dam )/ DNA cytosine methylation ( dcm ) that methylation pattern of plasmid DNA has a major impact on transformation efficiency and allows plasmid DNA to circumvent host restriction mechanisms [24-26]. …”
Section: Introductionmentioning
confidence: 99%
“…Taken together, it is concluded that the adenine methylation modification system in Thermoanaerobacter sp. X514 was active and is likely the major restriction modification system in this organism, suggesting that methylation of foreign DNA by specific methylases or cell extracts [22] is essential prior to introducing into X514 cells.…”
Section: Resultsmentioning
confidence: 99%
“…X514 were prepared from stationary-phase cells as described previously with minor modifications [22]. Briefly, cells from 100 ml stationary-phase culture of X514 were collected by centrifugation (3,500 g for 10 min), washed once with 100 ml chilled PENP buffer (10 mM KH 2 PO 4 -K 2 HPO 4 , 10 mM EDTA, 50 mM NaCl and 0.2 mM PMSF, pH 7.0), and then resuspended in 4 ml of the same buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-and short-filament cell extracts (CEs) were prepared as described previously, with modifications (18,19). Briefly, cultures were harvested from mid-log-phase cells by centrifugation at 5,000 ϫ g at 4°C for 15 min, and the cell pellets were washed twice with chilled 0.1 M PBS (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%